(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper seeks to study the Role of SEBI in Promoting Green Bonds and Sustainable Financing. The Securities and Exchange Board of India (SEBI) plays a pivotal role in fostering green bonds and sustainable financing within the Indian financial landscape. Green bonds are specialized financial instruments designed to fund projects with environmental benefits, such as renewable energy, clean transportation, and sustainable infrastructure. These bonds not only attract environmentally conscious investors but also align capital flows with sustainable development goals, crucial for addressing climate change and promoting green growth. SEBI’s regulatory framework for green bonds ensures transparency, credibility, and accountability in the market. Established guidelines define eligible green projects, specify the use of proceeds, mandate disclosure requirements, and encourage external reviews or certifications to verify the environmental credentials of issuers. This framework not only mitigates greenwashing risks but also instills investor confidence in the integrity of green investments.